Conformational Change of H64 and Substrate Transportation: Insight Into a Full Picture of Enzymatic Hydration of CO2 by Carbonic Anhydrase - Fu, Yuzhuang; Fan, Fangfang; Zhang, Yuwei; Wang, Binju; Cao, Zexing (Frontiers in Chemistry, 2021)
The enzymatic hydration of CO2 into HCO3− by carbonic anhydrase (CA) is highly efficient and environment-friendly measure for CO2 sequestration. Here extensive MM MD and QM/MM MD simulations were used to explore the whole enzymatic process, and a full picture of the enzymatic hydration of CO2 by CA was achieved. Prior to CO2 hydration, the proton transfer from the water molecule (WT1) to H64 is the rate-limiting step with the free energy barrier of 10.4 kcal/mol, which leads to the ready state with the Zn-bound OH−. The nucleophilic attack of OH− on CO2 produces HCO3− with the free energy barrier of 4.4 kcal/mol and the free energy release of about 8.0 kcal/mol. Q92 as the key residue manipulates both CO2 transportation to the active site and release of HCO3−. The unprotonated H64 in CA prefers in an inward orientation, while the outward conformation is favorable energetically for its protonated counterpart. The conformational transition of H64 between inward and outward correlates with its protonation state, which is mediated by the proton transfer and the product release. The whole enzymatic cycle has the free energy span of 10.4 kcal/mol for the initial proton transfer step and the free energy change of −6.5 kcal/mol. The mechanistic details provide a comprehensive understanding of the entire reversible conversion of CO2 into bicarbonate and roles of key residues in chemical and nonchemical steps for the enzymatic hydration of CO2.